Effects of ambient temperature on tropical hibernation in the lesser hedgehog tenrec, Echinops telfairi - Wein, Jens (Staats- und Universitätsbibliothek Hamburg Carl von Ossietzky, 2010)
Energy in the form of food is a important resource for animals. This is especially true for mammals which use considerably more energy than ectotherms. Evolution has thus led to diverse adaptations that lower energy consumption. Mammals from temperate and arctic regions often use torpor and hibernation to save energy. Torpor and hibernation are physiological states that are characterized by a reduced body temperature and metabolic rate. Hibernation bouts can last from several days up to several weeks and are interrupted by short and energetically-costly arousals during which the animals warm until they reach normal body temperatures. However, animals from the tropics can use torpor and hibernation as well, albeit at higher ambient temperatures. These higher ambient temperatures could affect energy consumption. Depending on the choice of hibernaculum, tropical hibernators are not only exposed to high ambient temperatures but also to significant daily fluctuations of ambient temperature. This in turn could affect the frequency as well as the energetic costs of arousals since fluctuating ambient temperatures offer the opportunity of passive heating to aid restoration of normal body temperature. The effect of ambient temperature on hibernation by a tropical mammal, the lesser hedgehog tenrec (Echinops telfairi), was investigated. E. telfairi is a small insectivore weighing 140 g, that is endemic to Madagascar and superficially resembles a European hedgehog. From a total stock of 27 animals, a randomized sample of tenrecs was exposed to different ambient temperatures in a climate chamber. The experimental regimes included constant and fluctuating ambient temperatures both during the summer (Sconst: 25°C and Sfluc: 20-30°C) and during the winter (Wconst: 20°C, Wlow: 15°C and Wfluc: 15-25°C). Energy consumption of the animals was measured by respirometry while the animals stayed within nestboxes in the climate chamber. Body temperature was measured with miniaturized temperature loggers (iButton), that were taped to the ...